Determinan Transfer Pricing Pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Suwandi, Eko Darmawan; Syarifudin, Achmad (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
Transfer pricing is used to determine prices for goods and services traded from subsidiaries to other subsidiaries or to the parent company. The price set is not in accordance with the reasonable market price. Multinational companies implement transfer pricing policies to reduce taxes paid by manipulating the prices of goods traded to related parties of the company. The aim of this research is to find out what factors can influence companies in carrying out transfer pricing. The dependent variable examined in this research is transfer pricing. The independent variables in this research consist of taxes, foreign ownership, company size, and leverage. This type of research is quantitative research that tests the influence between hypothesized variables through the presentation of numerical data. The data used in this research is secondary data sourced from the financial reports of mining companies listed on the Indonesia Stock Exchange for 2019-2023. The sample in this research was determined using the purposive sampling method. The analysis technique used in the research is multiple linear regression analysis with the help of the IBM SPSS version 21 program. The results of this research show that tax has a significant positive effect on transfer pricing, foreign ownership has a significant positive effect on transfer pricing, leverage has a significant positive effect on transfer pricing, and Company size has no effect on transfer pricing.